(untitled) (Research, Society and Development, 2020)
Purpose: to describe the children‘s profile seeking speech-language therapy with complaints of learning difficulties and to verify the association between children’s school performance and parents’ schooling and the agreement between the complaint and the diagnosis. Methods: data collection was performed in speech-language records of a school clinic. The following information was collected: date of birth, sex, date of screening, age presented on the date of screening and this year, education of the child on the date of screening and current, education of parents / guardians, type of speech therapy complaint, origin of the referral and the diagnostic impression. Data were analyzed using SPSS version 20 for Windows®. Results: of the 75 screenings analyzed, the majority were male children (66.77%). The average age of children with learning complaints was 9.25 at the time of screening. Despite the learning difficulty, only 24% of children failed the year. According to statistical analysis, it was observed that the children’s school performance is dependent only on the mother’s education. Most children were referred to the service by the teacher (58.7%). There was a weak agreement (K = 0.278; p = 0.001) between the complaint presented and the diagnostic impression. Conclusion: It was possible to draw a profile of children who have learning difficulties in the service studied. The mothers’ schooling can influence the children’s school performance, in addition to low agreement between the complaint and the diagnostic impression.